Self‐Assembly of TbPc2 Single‐Molecule Magnets on Surface through Multiple Hydrogen Bonding. Issue 5 (11th December 2017) - Pedrini, Alessandro; Poggini, Lorenzo; Tudisco, Cristina; Torelli, Martina; Giuffrida, Antonino E.; Bertani, Federico; Cimatti, Irene; Otero, Edwige; Ohresser, Philippe; Sainctavit, Philippe; Suman, Michele; Condorelli, Guglielmo G.; et al.
Abstract: The complexation between 2‐ureido‐4[1H]‐pyrimidinone (UPy) and 2, 7‐diamido‐1, 8‐naphthyridine (NaPy) is used to promote the mild chemisorption of a UPy‐functionalized terbium(III) double decker system on a silicon surface. The adopted strategy allows the single‐molecule magnet behavior of the system to be maintained unaltered on the surface. Abstract : A strategy based on multiple hydrogen bonding leads to a monolayer of terbium double decker molecules assembled on silicon maintaining unaltered their single molecule magnet behavior.